2012
DOI: 10.1007/s00464-012-2294-4
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic complete mesocolic excision for right colon cancer

Abstract: Background. To treat colon cancer via complete meso-colic excision (CME) with central vascular ligation (CVL), dissection along the embryologic fusion planes is required. However, this surgery is difficult, especially for right-sided colon cancer, because the anatomy and embryology of the transverse mesocolon are not familiar to gastrointestinal surgeons. Methods. In this video article, the anatomic details of the transverse mesocolon based on embryology are illustrated with a focus on the venous anatomy. Diss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
60
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(68 citation statements)
references
References 30 publications
5
60
1
2
Order By: Relevance
“…The mean operation time in the present study was found to191.6min. The means of the length of hospital stay (13.9 days), time to sips of water (4.7 days), time to soft diet (7.7 days), and blood loss (85.6 ml) in the present study were similar to those reported in previous studies [18][19][20][21]. Specimens were collected most often from the correct anatomical plane in colon cancer resection (92% vs. 40%, p<0.0001) and had a higher number of harvested lymph nodes (30 vs. 18, p<0.0001) than non-CME specimens [7].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The mean operation time in the present study was found to191.6min. The means of the length of hospital stay (13.9 days), time to sips of water (4.7 days), time to soft diet (7.7 days), and blood loss (85.6 ml) in the present study were similar to those reported in previous studies [18][19][20][21]. Specimens were collected most often from the correct anatomical plane in colon cancer resection (92% vs. 40%, p<0.0001) and had a higher number of harvested lymph nodes (30 vs. 18, p<0.0001) than non-CME specimens [7].…”
Section: Discussionsupporting
confidence: 90%
“…The most commonly occurring complications were found to be ileus and wound dehiscence. The mean operation time of CME in previous studies ranged from 136-269 min, and no significant differences were reported between open and laparoscopic surgeries [21,22]. The mean operation time in the present study was found to191.6min.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…The procedure is also oncologically safe for treating patients with colon cancer [3,4]. Complete mesocolic excision with central vascular ligation has been found to standardize colon cancer surgery, reduce local recurrence, and improve long-term survival [5,6], and the feasibility and safety of complete mesocolic excision in open and laparoscopic surgery have been demonstrated [7,8,9,10,11,12]. …”
Section: Introductionmentioning
confidence: 99%